2018
DOI: 10.4081/ija.2018.1197
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical properties, nitrogen uptake and grain quality of maize (Zea mays L.) as affected by tillage systems and nitrogen application

Abstract: Soil compaction is a global issue pertaining to agricultural lands. The frequent use of farm machinery and field operations at the same depth are the major causes of soil compaction. The gradual increase in soil compaction deteriorates maize grain quality due to reduced nitrogen (N) uptake. Quality food production by reducing soil compaction is the need of time, which can be achieved through deep tillage and N management. In this study, three tillage systems viz. conventional tillage (using cultivator), tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The higher the amount of N fertiliser applied, the greater the protein content in maize grains is [20], even though the correlation between GY and protein content for the higher N rate was negative (r = −0.193), indicating that the application of 240 kg N ha −1 was more directed towards GY increase than protein content increase in maize grain. Contrary to proteins, the starch content was negatively affected by the greater N application [46] and was the highest in the N1 treatment without the N fertiliser, 72.64%. Results of the study carried out by Singh et al [18] showed that maize GY increased from 10.5 t ha −1 with no N application, to 11.5 t ha −1 at the higher N3 level of 202 kg N ha −1 .…”
Section: Effects Of N Levels On the Maize Yield And The Grain Composimentioning
confidence: 80%
See 2 more Smart Citations
“…The higher the amount of N fertiliser applied, the greater the protein content in maize grains is [20], even though the correlation between GY and protein content for the higher N rate was negative (r = −0.193), indicating that the application of 240 kg N ha −1 was more directed towards GY increase than protein content increase in maize grain. Contrary to proteins, the starch content was negatively affected by the greater N application [46] and was the highest in the N1 treatment without the N fertiliser, 72.64%. Results of the study carried out by Singh et al [18] showed that maize GY increased from 10.5 t ha −1 with no N application, to 11.5 t ha −1 at the higher N3 level of 202 kg N ha −1 .…”
Section: Effects Of N Levels On the Maize Yield And The Grain Composimentioning
confidence: 80%
“…The interaction of the soil tillage system and the N rate with the year of investigation very significantly influenced all observed parameters, while the interaction of soil tillage and the N rate was significant for majority of the tested parameters, but not for the GSH, phenols and Phy content. Results obtained by Wasaya et al [46], proved that interactions between deeper soil tillage and a higher N level did not significantly affect either yield or the contents of oil, protein and starch in maize grain. In this research, it was demonstrated that lower N inputs and lesser intensive tillage (T1 and T2) were more important for the accumulation of starch, oil, and P i in grain.…”
Section: Interaction Of Factors Affecting Maize Yield and Qualitativementioning
confidence: 89%
See 1 more Smart Citation
“…The starch content of SYN5 under HN was higher than that under LN, whereas YN7 exhibited a different trend ( Figure ). Moderate N rates enhanced starch accumulation in rice, wheat, and normal maize . The high starch content under MN might be attributed to the increased number of cells and starch granules in the endosperm because of the enhanced activities of soluble and bound invertases and sucrose synthase .…”
Section: Resultsmentioning
confidence: 98%
“…Водночас у посушливі роки зернова продуктивність культури у разі мінімального обробітку ґрунту була вищою, ніж при традиційному [13]. Проведені дослідження інших авторів також підкреслюють позитивний вплив різних систем обробітку ґрунту на урожай і показники якості зерна кукурудзи [14][15][16].…”
Section: вступunclassified